2013
DOI: 10.1186/1471-2318-13-63
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of familiarity on faucet usability for older adults with dementia

Abstract: BackgroundChanges in cognition caused by dementia can significantly alter how a person perceives familiarity, impacting the recognition and usability of everyday products. A person who is unable to use products cannot autonomously complete associated activities, resulting in increased dependence on a caregiver and potential move to assisted living facilities. The research presented in this paper hypothesised that products that are more familiar will result in better usability for older adults with dementia. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…▪ COACH's development team conducted research to specifically investigate assumptions (e.g., [47][48][49][50] 53 ; the usability of different types of water faucets by people with dementia 54 ; babyboomer and older adults' perceptions regarding the acceptability of different types of sensors in different areas of the home 50 ; and the use of actors simulating dementia to optimise pre-trial prototypes 55 .…”
Section: Transformationmentioning
confidence: 99%
“…▪ COACH's development team conducted research to specifically investigate assumptions (e.g., [47][48][49][50] 53 ; the usability of different types of water faucets by people with dementia 54 ; babyboomer and older adults' perceptions regarding the acceptability of different types of sensors in different areas of the home 50 ; and the use of actors simulating dementia to optimise pre-trial prototypes 55 .…”
Section: Transformationmentioning
confidence: 99%
“…Care partner (P15) The perspectives of the participants on this issue finds supporting evidence from research that suggests the more familiar people with dementia are with their environment the more likely they are to retain skills and act independently (Brittain et al, 2010;Provencher et al, 2012;Boger et al, 2013. ) For example, Provencher et al (2012) found older people with 'poor and preserved executive functions' to perform cooking tasks more effectively at home than in unfamiliar surroundings.…”
Section: Barriers Of a Move To Shared Carementioning
confidence: 88%
“…Therefore, if dementia develops, the person will recognise the device and permit its guidance, because it is familiar and trusted. However, whilst addressing the affective aspect of trust is probably essential for achieving actual use of ATDs, the theory that addressing trust through long-term use will solve this challenge, as indicated in one study (Boger et al 2013), requires further investigation. An alternate solution is discussed in case study 2, below.…”
Section: Adaptable Decision-making Supportmentioning
confidence: 97%
“…Mild cognitive impairment (MCI) is a prodromal stage of dementia (Petersen and Negash 2008). There is evidence that suggests that familiarity with a device determines its usability until more advanced stages of dementia (Boger et al 2013). By introducing adaptive ATDs whilst people are experiencing MCI, the device becomes a standard part of everyday life.…”
Section: Adaptable Decision-making Supportmentioning
confidence: 99%